Characterisation of banana wine fermented with recombinant wine yeast strains - Byaruagaba-Bazirake, George William; Pierre, van Rensburg; Kyamuhangire, William (American Journal of Food and Nutrition, 2013)
Commercial enzyme preparations are applied in the process of winemaking to improve wine processing and wine quality. In this study, three recombinant wine yeast strains that had been developed to improve wine processing were compared with regard to their ability to produce banana wine of an acceptable quality. The recombinant wine yeast strains contain genes coding for enzymes able to degrade different polysaccharides (glucan, xylan, pectin and starch). The recombinant strains were able to induce higher wine yields from the fermented banana pulp vis-à-vis the control. The wines obtained with the recombinant strains and the untransformed control did not show significant differences (p>0.05) in their physicochemical parameters. The highest wine yield obtained from the pulp which was treated with genetically modified yeast (recombinant yeast strain) secreting glucanase and xylanase enzymes (plasmid pDLG39) was 69.5% v/w prepared from Bogoya pulp. This wine yield was higher than the control yield (65.9± 0.07) by an increase of 5.5% v/w. However, the wine from Kayinja pulp which was treated with genetically modified yeast secreting pectinase enzyme(plasmid pPPK) yielded wine (60.3±0.28% v/w) with 35% increase compared to the wine (44.7±0.49) obtained with the control yeast. The recombinant yeast strains compared in this work secreted enzymes playing a similar role to that of the previously studied pectinolytic commercial enzymes. Therefore, such a recombinant yeast strain could be used in banana wine fermentations as an alternative to commercial enzyme preparations
Keywords: Recombinant yeast; pectinase; glucanase; xylanase; amylase; wine